(untitled) (Economic and Political Thought, 2018)
The author of the article supports the thesis that culture and cultural factors should be incorporated into the theory of economics. It is often postulated that this theory reflects reality better and thus one solution is proposed in the article. Attention is drawn to the fact that the notion of culture is inaccurate and many definitions exist. Methodological problems may be one reason for the lack of interest of economists in this topic. The author accepts the definition associated with values and thus eliminates a narrow understanding of culture through the prism of art and creative industries. It is demonstrated in the article that even though the issue is relatively new, there are historical grounds for it. The connection between cultures and economics as well as methodological remarks on further research are shown. The author tries to omit problems that have already been discussed in the relatively scarce literature.